Pengembangan Perangkat Ajar Inklusif Berbasis Diferensiasi dengan Integrasi Kompetensi Sosial Emosional untuk Menjawab Kebutuhan Belajar Peserta Didik Reguler dan Berkebutuhan Khusus - Shibi Zuharoul Mardliyah; Mazrikhatul Miah; Iftitahun Nabilah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study focuses on the development of inclusive teaching devices designed through a differentiated approach and the integration of Social-Emotional Competencies (SEC), aimed at addressing the learning needs of both regular students and those with special needs. The learning focus is on the topic of Indonesia’s Cultural Heritage. This research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the study indicate that the developed teaching devices are valid based on evaluation through the Platform Merdeka Mengajar (PMM) and have proven effective in improving the achievement of learning objectives, active participation of students, as well as generating positive responses to the learning process. Challenges encountered during implementation related to the students' lack of experience in participating in differentiated learning and experimental activities. However, these challenges were addressed through targeted and continuous guidance.